Paciente de sexo femenino de 12 años de edad con insuficiencia renal crónica - Triana Díaz, Yuleisi Viviana (2021)
Due to the high prevalence of chronic kidney disease and the resulting high costs which turn out to be a great discomfort for the population, it is currently a public health problem in our country. Understanding the definition and classification of the disease is an important point for early diagnosis and successful treatment of the disease. Early detection of chronic kidney failure (CKD) can prolong the functional life of the kidneys and reduce the number of dialysis cases and the risk of death from cardiovascular disease. When the glomerular filtration rate reduces more than 50%, it is necessary to quickly treat the patient: take all necessary measures to try to reduce the rate of degeneration of kidney failure, ensure good control of homeostasis and protect the two main threatened organs, the cardiovascular and osteoarticular systems. Treatment techniques for end-stage renal failure are hemodialysis, peritoneal dialysis, and kidney transplantation. If necessary, these therapies can be used in combination to ensure a very long survival period, which is now more than 30 years and what has yet to be developed until a more effective treatment is found. There are extra-renal factors that determine survival: age, especially related systemic diseases, such as diabetes and cardiovascular diseases. All efforts should focus on better defining the risk groups for kidney failure, early detection of diseases in these groups, and better prevention through proper nutrition.